Seroprevalence of porcine reproductive and respiratory syndrome virus on swine farms in a tropical country of the Middle Americas: the case of Costa Rica - Guzmán, Mónica (2021)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes signifcant economic losses to the swine industry worldwide. Little is known regarding the epidemiology of this infection in tropical countries. To address this problem in Costa Rica, a seroepidemiological study was carried out in two phases. In the frst phase, a pilot study was conducted in nine farms with the clinical diagnosis of PRRSV. In total, 265 pig serum samples were collected from animals ranging in age from 1 to 15 weeks of age. This study aimed to establish the duration of maternal immunity in piglets, to identify the period of viremia, and to determine when seroconversion occurs. In the second phase, a cross-sectional serology study was performed on a representative sample of the Costa Rican national herds in the second phase. The twenty-fve selected farms represent all provinces and were classifed according to herd size (100 to 2000 sows). In each farm, pigs aged 8, 10, and 12 weeks were sampled, as well as gilts based on the pilot study. In total 1281 pigs were sampled across all 25 farms. The aim of the cross-sectional study was to quantify the seroprevalence of PRRSV in Costa Rican pig farms and to describe its geographical distribution in this tropical country. The prevalence of positive farms was 44% (11/25), and these farms were located in six of the seven provinces of Costa Rica. Overall, 58% (344/596) of the pigs were seropositive to PRRSV. The age of the pigs and the ecozone where farms were located were signifcantly related with PRRSV seroprevalence in animals and herds, respectively.